2022
DOI: 10.1111/dar.13505
|View full text |Cite
|
Sign up to set email alerts
|

Case series on treatment of dependence to Kamini Vidrawan Ras with opioid substitution therapy

Abstract: Introduction: A cohort of clients was recognised attending an addiction medicine clinic with similar presentations of opioid dependence from use of a rarely known Ayurvedic medication in a specific ethnic community. This retrospective case series was completed to promote wider recognition and further understanding of dependence on Kamini Vidrawan Ras (Kamini). Methods: A retrospective file audit of the electronic medical record for clients of an addiction medicine outpatient clinic with a history of dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The Kamini tablets containing opiates were noted as the main drug of concern being supplied by these stores. These findings concur with the cases identified by previous studies done in Australia [1,9] as well as an investigation by Punjabi community radio in Australia that found Kamini tablets to be readily available as herbal products [10].…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The Kamini tablets containing opiates were noted as the main drug of concern being supplied by these stores. These findings concur with the cases identified by previous studies done in Australia [1,9] as well as an investigation by Punjabi community radio in Australia that found Kamini tablets to be readily available as herbal products [10].…”
supporting
confidence: 91%
“…Perhaps surprisingly, alcohol was also noted to be on the rise among women within this community. Alcohol consumption together with Kamini consumption was noted as a concurrent factor by Naren et al [1] and Khan et al [9] in their study in south-east Queensland.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Two recently published unrelated case series have highlighted the issue of increasing presentations for opioid use disorder following use of Kamini, especially in patients from Southeast Asian communities. The first case series by Khan et al [1] described 12 cases identified through addiction clinics in South East Queensland, quickly followed by a second series by Naren et al of 12 patients in Melbourne [1,2]. Almost all the cases reported in both series were males from India.…”
mentioning
confidence: 99%